Design and Validation of Tourism Destination Marketing Model Using New Electronic Technologies - Fatemeh Mirzaei; Hamid zargham boroujeni; Farid Askari; Seyed Mahdi Moafi Madani (گردشگری و اوقات فراغت)
This study was conducted with the aim of designing and validating the marketing model of tourist destinations using modern electronic technologies. From the point of view of the purpose of this study, it is applied-developmental research, and from the point of view of the method and time period of data collection, it is included in the category of survey-cross-sectional studies. Also, because both quantitative and qualitative methods have been used, it is mixed research. The statistical population of this article in the qualitative phase includes experienced professors and experts in the tourism industry, which was used in a targeted way from the perspective of 24 people. Also, in a small part, the point of view of 384 tourists was used. In this article, the theme analysis method has been used to identify the underlying categories of tourism destination marketing using modern electronic technologies. The partial least squares method has also been used to validate the model. Data analysis was done with MaxQDA and Smart PLS software. Findings: The results have shown that political-economic conditions, governmental support and cultural-social conditions affect new electronic technologies and digital transformation. These factors have an effect on tourism infrastructures and empowerment of tourism facilities and lead to awareness of the destination brand, tourist experience management and multi-sensory marketing. Through improving the awareness of the destination brand, tourist experience management and multi-sensory marketing, the marketing of tourist destinations becomes possible.